THE RESEARCH ON FEMALE MOTIVATION FOR ENTREPRENEURSHIP IN THE REPUBLIC OF SERBIA - Popović, Blaženka; Paunović, Tamara; Maletić, Radojka (International Journal of Economic Practice and Policy, 2021)
Globalization, internationalization and overall technologization bring in a number of significant changes in modern business, and parallely with this, an increasing trend is growing presence of women in the business field as entrepreneurs. The main focus of the paper is to determine the significance of different entrepreneurial motivation defined by female entrepreneurs in the Republic of Serbia, depending on their age, education level, marital status, length of service and number of employees. Empirical research was conducted on a sample of 162 female entrepreneurs on the territory of the Republic of Serbia. The data were analyzed using factor analysis, Mann-Whitney U and Kruskal-Wallis test. The research results indicate that the motivation for entrepreneurship can be grouped into two key dimensions, or two factors. Non-parametric tests have found that there are differences in the significance of different motivation for women entrepreneurs of different age, education level, marital status, length of service and number of employees. The results of the research confirm that not all female entrepreneurs have the same opinion regarding the preferences of certain motives for entrepreneurship.